Cervical ectopic pregnancy treated with methotrexate - Solís, H. (2015)
We report two cases of cervical pregnancy with desire of childbearing capacity preservation. Both patients were sucessfully treated with 50 mg-m2 single dose methotrexate therapy, free of complications.